2014
DOI: 10.1111/cogs.12184
|View full text |Cite
|
Sign up to set email alerts
|

Do Lemmas Speak German? A Verb Position Effect in German Structural Priming

Abstract: Lexicalized theories of syntax often assume that verb-structure regularities are mediated by lemmas, which abstract over variation in verb tense and aspect. German syntax seems to challenge this assumption, because verb position depends on tense and aspect. To examine how German speakers link these elements, a structural priming study was performed which varied syntactic structure, verb position (encoded by tense and aspect), and verb overlap. Abstract structural priming was found, both within and across verb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Chang, Baumann, Pappert, & Fitz, 2014;Flecken, Gerwien, Carroll, & von Stutterheim, 2015;Jaeger & Norcliffe, 2009, for language production). Moreover, our study provides a methodological improvement by testing participants in their second language rather than their native language.…”
Section: Discussionmentioning
confidence: 99%
“…Chang, Baumann, Pappert, & Fitz, 2014;Flecken, Gerwien, Carroll, & von Stutterheim, 2015;Jaeger & Norcliffe, 2009, for language production). Moreover, our study provides a methodological improvement by testing participants in their second language rather than their native language.…”
Section: Discussionmentioning
confidence: 99%
“…'s study (Chang, Dell, & Bock, ). Second, the model can learn typologically different languages (Chang, Baumann, Pappert, & Fitz, ) and, in particular, it has been shown to be able to learn and explain various Japanese phenomena (Chang, ), which is a verb‐final case‐marked language like Korean. Finally the model uses linguistic input to make small changes to its morphosyntactic knowledge within a limited capacity memory and this means that the knowledge that it learns for different rules may compete with or support learning of new rules (Fitz, Chang, & Christiansen, ; Twomey et al., ).…”
Section: A Connectionist Model Of the Acquisition Of Morphosyntactic mentioning
confidence: 99%
“…Chang, Baumann, Pappert, and Fitz (2015) found that German-speaking participants showed stronger priming effects when constructing verb-second sentences from a list of words (e.g., uberreichen Pförtner Schlüssel Mitarbeiter [hand doorman key co-worker]) after listening to prime sentences that were also verb-second (e.g., Die Großmutter schickt ihrem Enkel ihr Testament [The grandmother sends her grandson her will] than after prime sentences that were verb-final ( Die Großmutter hat ihrem Enkel ihr Testament geschickt [literally, The grandmother has her grandson her will sent]. That is, the priming effect was larger when verb position matched between prime and target than when it mismatched.…”
Section: Structural Priming From Anomalous Sentencesmentioning
confidence: 99%